Translation strategies in the Indonesian subtitles of the Women Talking movie: A study based on Gottlieb’s translation theory - Auliya Ramdini; Baharuddin Baharuddin; Lalu Jaswadi Putera; Ahmad Zamzam (Universitas Islam Sultan Agung, 2026)
Audio-visual translation (AVT) is an essential part of making films accessible across languages and cultures. However, there are few research on subtitling procedures in films with social and ideological complexity. This study aims at analyzing the types of translation strategies employed in the Indonesian subtitles of “Women Talking” (2022) based on Gottlieb’s classification of translation strategies (1992) as well as investigating the most frequently used translation strategies used in the Indonesian subtitles of the movie. Using a descriptive qualitative approach, a total of 300 of 1,318 subtitle units were purposively selected and analyzed using documentation and qualitative content analysis. The findings showed that 8 out of 10 Gottlieb’s translation strategies were identified that included Transfer, Paraphrase, Condensation, Imitation, Expansion, Deletion, Decimation, and Resignation strategies, while Transcription and Dislocation were absent. Transfer strategy is the most frequently used strategy with 160 occurrences (53.33%), followed by Paraphrase (50 occurrences, 16.67%), Condensation (30 occurrences, 10.00%), Imitation (17 occurences, 5.67%), Expansion (15 occurences, 5.00%), Deletion (15 occurences, 5.00%), Decimation (12 occurences, 4.00%), and Resignation (1 occurence, 0.33%). The prevalent use of Transfer strategy suggests the translator’s preference for retaining the original content via literal translation, but Paraphrase and Condensation were used to address linguistic and technical limits of subtitling. The results indicate that the translation of Indonesian subtitles of Women Talking put semantic correctness at the top of the priority list while still keeping the readability for Indonesian viewers.